THE EFFECT OF REALIA MEDIA BASED ON REALISTIC MATHEMATICS EDUCATION ON NUMERACY LITERACY ABILITY - Suryaningsih, Tri; Edwita; Gusti Yarmi (AULADUNA: Jurnal Pendidikan Dasar Islam, 2023)
Abstract Numeracy skills at elementary schools play an essential role as a fundamental foundation for students in developing logical thinking, problem-solving, and mathematical skills needed to face the complexity of technological developments. This study aims to investigate the effect of using Realistic Mathematics Education (RME)-based realia media on numeracy literacy skills in Class IV students at SD Negeri Gandaria Utara 03 South Jakarta. The research method applied was a quasi-experiment. The sample consisted of IVA class students as the experimental class and IVB class students as the control class, which were selected using simple random sampling. The research instrument was a test consisting of 6 essays. The research results showed that using RME-based realia media had a significant effect on students’ numeracy literacy skills. Thus, teachers can consider the use of RME-based realia media as an effective teaching tool to improve students’ numeracy literacy skills. The main implication of this research is the importance of using realia in learning mathematics. Teachers and educators can utilize real and textual objects in teaching mathematical concepts to help students understand them better.